1985
DOI: 10.1093/jn/115.7.849
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wheat Bran, Pectin and Cellulose on the Secretion of Bile Lipids in Rats

Abstract: We assayed the lipid content of bile from rats that had been fed either a standard diet (5% fat) or a high fat diet (25% fat, 1.2% cholesterol) in the presence or in the absence of various dietary fibers (namely, wheat bran, pectin and cellulose). The cholesterol concentration in bile from rats fed the high fat diet plus wheat bran or pectin was lower than that of the rats fed the high fat, high cholesterol diet without fiber. Bile phospholipids did not vary significantly from one group to another. In comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

1986
1986
1997
1997

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
1
11
2
Order By: Relevance
“…The present data may thus explain the lack of influence of purified cellulose gener ally observed, in the long term, on blood lipid levels [2][3][4][5][6]26] and on lipid hepatic storage [2][3][4][5][6] and secretion [7],…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The present data may thus explain the lack of influence of purified cellulose gener ally observed, in the long term, on blood lipid levels [2][3][4][5][6]26] and on lipid hepatic storage [2][3][4][5][6] and secretion [7],…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have already been per formed in animal models in order to study the metabolic effects of cellulose. Long-term feeding of rats with diets enriched with 5-20% cellulose did not significantly alter the concentration of cholesterol and lipids in plasma, liver or bile [2][3][4][5][6][7], Other studies have described some effects of cellulose on the ultrastructure of the intestinal mucosa [8] or on the intestinal resynthesis of phospholipids [9], More recently, it was suggested that cellu lose might shift the site of fat absorption more distally in the small intestine [10].…”
Section: Introductionmentioning
confidence: 99%
“…Our studies favor a role for calcium pectate in the observed binding of bile acids to plant cell wall residue. It remains to be seen if calcium pectate will have a greater hypocholesterolemic effect than has been reported for commercial pectins in feeding studies (11)(12)(13)(14)(15).…”
Section: Resultsmentioning
confidence: 97%
“…Indeed, the total amount of bile and biliary components that are passing through the bile duct to the bowel have been poorly investigated. According to the few studies available, bile flow is either stimulated (Ikegami et al 1984;Lafont et al 1985) by dietary fibre consumption. It is interesting to parallel the usual choleresis due to dietary fibre and the strikingly high bile flow in herbivores.…”
Section: Bile R E S P O N S E T O D I E T a R Y F I B R E Choledocal mentioning
confidence: 99%
“…Total bile salt secretion rate has been found to be either increased or unaffected according to the type of dietary fibre (Ikegami et al 1984), to the basal diet used (Lafont et al 1985), to the initial physiopathological state of the subjeqs (Meyer el There are only a few studies dealing with the effect of fibre-enriched diets on cholesterol concentration in bile, and wheat bran was used in nearly all of them. Cholesterol concentration is usually unchanged (Huijbregts et al 1980a;Klapdor & Hein, 1982;Lafont et al 1985;Payne et al 1989) and sometimes increased (Lafont et al 1985) after dietary fibre supplementation, provided that the bile is initially unsaturated. The concentration of cholesterol in the bile of lithiasic patients given supplements of bran, however, decreases (Watts et al 1978).…”
Section: Bile R E S P O N S E T O D I E T a R Y F I B R E Choledocal mentioning
confidence: 99%